Editor MIDI para violão com articulação humanizada nota a nota e qualidade acústica em linguagem funcional pura - Menezes Júnior, Carlos Roberto Ferreira de (2007)
This work presents as main goal to implement a computational application that allows the user create MIDI musical sequences for guitar. The difference of the musical sequences generated by the software resides in the fact that each musical note of the MIDI sequence can be modified for the inclusion of humanized articulation, individualized and with timbral qualities like an acoustic instrument. The sound resulted of these sequences is render in other musical formats, such as Wave. The application interface and functions are developed in pure functional paradigm (based on lambda calculus). This choice avoids the use of dlls and other resources strongly dependent of operational system version. The choice of the functional language Clean is justified in this work, by the reason of being one of the two more efficient languages of the actuality (according to analysis of specialized benchmarks). In the implementation of the manipulation functions of SMF files and interface generated libraries that will allow extending this work for another soloists (monophonic) instruments. This application presents an adherent interface with all kinds of users. In order to manipulate SMF files, many libraries were developed, allowing extending this work for other soloists (monophonic) instruments. This application presents an adherent interface with all levels of users.